What Makes an Ideal Unemployed Person? Values and Norms Encapsulated in a Computerized Profiling Tool - Karolina Sztandar-Sztanderska; Marianna Zielenska (Social Work & Society, 2020)
This article provides insights into a computer-based profiling tool implemented in Poland from 2014 to 2019 to measure the employability of unemployed individuals and decide upon allocation of active labor market policies. We propose to treat the profiling tool as a source of information about what was expected from the unemployed citizens by state authorities and which attitudes were perceived by the state as "desirable" or "demanding adjustment." We show how the profiling technology served to shape the conduct of the unemployed population, and how it imposed upon them a certain ideal of social citizenship. Our findings indicate that the normative assumptions underlying the profiling relate directly to the key aspects of welfare state transformations, namely, to the new social contract which delegitimizes financial benefits and puts forward activation, to the new concept of a citizen as an entrepreneurial and self-reliant actor and to the new, individualized perception of social risks. Results are based on the analysis of the profiling questionnaire, scoring mechanism as well as the reconstruction of the policy-making process.